Innovative Surgical Approaches and Selection Criteria of Large Acne Keloidalis Nuchae Lesions. Issue 5 (May 2019) - Umar, Sanusi; David, Consuelo V.; Castillo, Jason R.; Queller, Jenna; Sandhu, Sophia
Abstract : Background: Acne keloidalis nuchae is a debilitating condition mainly affecting the occipital region or nape of the neck. Surgical approaches are limited in aesthetic outcomes. Three innovative surgical approaches based on selection criteria are presented for enhanced and more predictable wound healing and posterior hairline cosmesis. Methods: "Bat excision" and secondary intention healing are shown for 2 of 37 representative patients and confined to the area between the occipital protuberance superiorly and posterior hairline inferiorly. Lesions with ⩽3 cm vertical width were required to be in the lower one-half portion of this zone. The same procedure was aided by the use of tension sutures for lesions with >3 cm vertical width area within the defined zone. It was also suitable for breaches of the 2 horizontal lines defined above but generally located in the nuchal area. Debridement of premature epithelizing granulation tissue is shown in 2 additional patients. Results: Use of these procedures with debridement in selected patients allowed fine control over the hairline shape and resulted in narrower scars. The mean maximum sagittal width of excised lesions was 5.4 cm. Excised lesion width ≥6.5 cm was highly predictive of >2.5 cm wide scar ( P = 0.001). Conclusion: Innovative procedures based on selection criteria can extend the approach of acne keloidalis nuchae excision with secondary intention healing to better control the final hairline shape and minimize scarring.